철심형 전류변성기의 비오차 및 위상오차 절대 평가 기술의 확장 : 1차 전류 = $5\;kA{\sim}40\;kA - 김윤형; 한상길; 정재갑; 한상옥; Kim, Yoon-Hyoung; Han, Sang-Gil; Jung, Jae-Kap; Han, Sang-Ok (전기학회 논문지 P권, 57(4), 2008)
We have extended an absolute evaluation method to obtain the ratio error and phase displacement of a current transformer (CT) up to primary current of 40,000 A by measuring four parameters of equivalent circuit in CT. The method was applied to CTs under test with the current ratios in the range of 5,000 A / 5 A - 40,000 A / 5 A. The ratio error and phase displacement of the CTs under test obtained in this study are consistent with those measured at the national institutes in Canada and Germany using the same CTs under test within an expanded uncertainty (k = 2) in the overall current ratios.